2017
DOI: 10.1002/2017ja023947
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term variability in the ionosphere due to the nonlinear interaction between the 6 day wave and migrating tides

Abstract: Using the thermosphere‐ionosphere‐mesosphere electrodynamics general circulation model simulations, we investigate the short‐term ionospheric variability due to the child waves and altered tides produced by the nonlinear interaction between the 6 day wave and migrating tides. Via the Fourier spectral diagnostics and least squares fittings, the [21 h, W2] and [13 h, W1] child waves, generated by the interaction of the 6 day wave with the DW1 and SW2, respectively, are found to play the leading roles on the subd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 56 publications
3
68
8
Order By: Relevance
“…This has largely been made possible by the development and application of first‐principles general circulation models that solve the coupled equations governing the energetics, dynamics, electrodynamics, and chemistry of the stratosphere, mesosphere, thermosphere, and ionosphere. For instance, authors used the National Center for Atmospheric Research thermosphere‐ionosphere‐mesosphere‐electrodynamics general circulation model (TIME‐GCM) to demonstrate that PW themselves can penetrate above 100 km to produce dynamo electric fields that drive Q2DW (Yue et al, , ) and Q6DW (Gan et al, , ) F‐region ionospheric variability, although it is recognized that such penetration is highly sensitive to the zonal‐mean wind distribution above 100 km, which is poorly known. In addition, Yue et al (), Gan et al (), and Gu et al () show that the nonlinear interaction between PW and tides and the secondary waves that arise from these interactions play an important role in how the ionosphere responds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has largely been made possible by the development and application of first‐principles general circulation models that solve the coupled equations governing the energetics, dynamics, electrodynamics, and chemistry of the stratosphere, mesosphere, thermosphere, and ionosphere. For instance, authors used the National Center for Atmospheric Research thermosphere‐ionosphere‐mesosphere‐electrodynamics general circulation model (TIME‐GCM) to demonstrate that PW themselves can penetrate above 100 km to produce dynamo electric fields that drive Q2DW (Yue et al, , ) and Q6DW (Gan et al, , ) F‐region ionospheric variability, although it is recognized that such penetration is highly sensitive to the zonal‐mean wind distribution above 100 km, which is poorly known. In addition, Yue et al (), Gan et al (), and Gu et al () show that the nonlinear interaction between PW and tides and the secondary waves that arise from these interactions play an important role in how the ionosphere responds.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, authors used the National Center for Atmospheric Research thermosphere‐ionosphere‐mesosphere‐electrodynamics general circulation model (TIME‐GCM) to demonstrate that PW themselves can penetrate above 100 km to produce dynamo electric fields that drive Q2DW (Yue et al, , ) and Q6DW (Gan et al, , ) F‐region ionospheric variability, although it is recognized that such penetration is highly sensitive to the zonal‐mean wind distribution above 100 km, which is poorly known. In addition, Yue et al (), Gan et al (), and Gu et al () show that the nonlinear interaction between PW and tides and the secondary waves that arise from these interactions play an important role in how the ionosphere responds. Other studies have shown that the dissipation of PW (Chang et al, ; Gan et al, ; Yue & Wang, ) or changes in turbulent mixing arising from PW modulation of GW (Nguyen & Palo, ) can induce chemical changes that translate to ionospheric variations, either at PW periods or in the net response.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary waves generated from the nonlinear interaction between tides and planetary waves may propagate upward and induce ionospheric variability (e.g., England et al, 2012;Yue et al, 2016;Gan et al, 2017). This way, we investigated the amplitude and phase vertical structures of the 0.75 cycles day −1 secondary wave shown in Fig.…”
Section: Interaction Between the Ufkw And The Diurnal Tidementioning
confidence: 99%
“…From the phase lag we estimated a vertical wavelength of approximately 44 km. This relatively long vertical wavelength (Forbes, 2000;Gan et al, 2017) may allow the secondary wave to penetrate into the Eregion dynamo and induce variability in the ionosphere. Such investigation, however, is outside the scope of this study.…”
Section: Interaction Between the Ufkw And The Diurnal Tidementioning
confidence: 99%
See 1 more Smart Citation